Murine retrovirus-induced spongiform encephalomyelopathy: host and viral factors which determine the length of the incubation period. - Czub, M (1992)
A molecular clone of wild mouse ecotropic retrovirus CasBrE (clone 15-1) causes a spongiform neurodegenerative disease with a long incubation period, greater than or equal to 6 months. This virus infects the central nervous system (CNS) at low levels. In contrast, a chimeric virus, FrCasE, containing env and 3' pol sequences of 15-1 in a Friend murine leukemia virus background, infects the CNS at high levels and causes a rapid neurodegenerative disease with an incubation period of only 16 days. With both viruses, the induction of neurologic disease is dependent on inoculation during the perinatal period. Since the length of the incubation period of this disease appears to be a function of the relative level of CNS infection, we have attempted to identify the viral and host factors which determine the relative level of virus infection of the CNS. It was previously shown that the CNS is susceptible to infection only during the perinatal period (M. Czub, S. Czub, F. J. McAtee, and J. L. Portis, J. Virol. 65:2539-2544, 1991). Here we have found that the susceptibility of the CNS wanes progressively or gradually as a function of the age of the host, this age-dependent resistance being complete by 12 to 14 days of age. Utilizing a group of chimeric viruses, we found that the relative level of CNS infection achieved after inoculation of mice at 1 day of age was a function of the kinetics of virus replication and spread in peripheral organs. Viruses which reached peak viremia titers early (5 to 7 days of age) infected the CNS at high levels, and viruses which reached peak titers later infected the CNS at lower levels. Among the group of viruses examined in the current study, the kinetics of peripheral virus replication and spread appeared to be influenced primarily by sequences within the R-U5-5' leader region of the viral genome. These results suggested that the relative level of CNS infection was determined very early in life and appeared to be a function of a dynamic balance between the kinetics of virus replication in the periphery and a progressively developing restriction of virus replication in the CNS.